Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 2 - Section 2.1 - The Additon Property of Equality - Exercise Set: 16

Answer

y = -3

Work Step by Step

$\frac{13}{11}y - \frac{2}{11}y$ = -3 Combine like terms: $\frac{11}{11}y$ = -3 Simplify: y = -3 Check with substitution: $\frac{13}{11}(-3) - \frac{2}{11}(-3)$ = -3 $\frac{-39}{11} - \frac{-6}{11}$ = -3 $\frac{-33}{11}$ = -3 -3 = -3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.